Timing and degree of left atrial stunning and reverse functional remodeling following electrical cardioversion in patients with recent onset atrial fibrillation. (25th November 2020) - Arvanitis, P; Johansson, A.K; Frick, M; Malmborg, H; Gerovasileiou, S; Larsson, E.M; Blomstrom Lundqvist, C
Abstract: Background: Atrial fibrillation (AF) results in left atrial electrical, structural and functional remodeling. Restoration of sinus rhythm hallmarks the beginning of reverse remodeling, the extent of which may depend on the type of AF. Purpose: The aim of the study was to assess resumption of left atrial function after electric cardioversion in patients with recent onset AF and to explore the association between reverse remodeling and the type of atrial fibrillation. Methods: Patients with AF duration <48 hours were prospectively included. Trans-thoracic echocardiography was performed prior, immediately after (2–4 hours) and 7–10 days following CV. Left atrial volume index (LAVI), left atrial global longitudinal strain during reservoir (LAGLS-res), conduit (LAGLS-cond) and contractile (LAGLS-contr) phases, left atrial ejection fraction (LAEF) and left ventricular ejection fraction (LVEF) were measured. Results: Forty-three patients (84% males) aged 55±9.6 years, (mean±SD), with median CHA2DS2-VASc score 1 (interquartile range 0–1) were included. Repeated measure analysis of variance revealed a statistically significant overall change for LAGLS-res F(2, 78)=55.4, p<0, 001, LAGLS-cond F(2, 78)=23.3, p<0, 001, LAGLS-contr F(2, 78)=39.7, p<0, 001, LAEF F(2, 80)=28.5, p<0.001 and LVEF F(2, 80)=8.4, p<0.001. At 7–10 days, LAGLS-contr 12±4%, LAEF 53±9% and LVEF 60±6 (mean±SD) return within normal reference intervals. Notably left atrial recovery seems to precede left ventricular recovery. No statistical significant interaction with the type of atrial fibrillation could be shown. Conclusion: Left atrial functional reverse remodeling occurs within ten days after successful electric cardioversion of patients with recent onset atrial fibrillation. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Swedish Heart-Lung Foundation, Correvio International Sárl (Geneva Switzerland), Selanders Stiftelse